STUDENTS’ SELF-AWARENESS AS A FACTOR OF PROFESSIONAL DEVELOPMENT - Daukeeva, Aidyn Oralbaevna (SCIENCE and SOCIETY, 2026)
This article provides scientific and theoretical information about the goal, worldview, experiences, change of situation and new formation of personality in the development of self-confidence of future teachers.
Keywords: educator; self-confidence; frontal lobe; self-control; self-defense; self-awareness